Analisis beban kerja pegawai department of engineering PT. Semen Indonesia (Persero) tbk menggunakan metode Full Time Equivalent (FTE) - Fadhli, Mohammad; Saifuddin, Joumil Aidil (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Problems such as fatigue, decreased performance, and high stress levels often arise as a result of workload imbalance, which can affect the operational efficiency of the company. Accurate workload analysis is essential to overcome this problem. This study aims to analyze the workload in the engineering department of PT Semen Indonesia using the Full Time Equivalent (FTE) method to evaluate workforce needs and distribute workload proportionally. Based on the results of the FTE calculation, the Integration Bureau Staff with 11 employees obtained a total FTE value of 12.7 ≈ 13, the Process Bureau Staff with 3 employees obtained a total FTE value of 4.7 ≈ 5, the Mechanical Bureau Staff with 4 employees obtained a total FTE value of 6.48 ≈ 6, the Civil Bureau Staff with 5 employees obtained a total FTE value of 6.48 ≈ 6, the Elins Bureau Staff with 3 employees obtained a total FTE value of 3.43 ≈ 3.